Guidelines for the prevention and treatment of travelers’ diarrhea: a graded expert panel report - Riddle, Mark S.; Zanger, Philipp (Journal of travel medicine, 2017)
Abstract. Background: Travelers’ diarrhea causes significant morbidity including some sequelae, lost travel time and opportunity cost to both travele